Microarray analysis of central nervous system associated with the infiltration of microglia in mice showing signs of paralysis after the intramuscular inoculation of RV (CVS-11 strain) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies occurs in worldwide and more than 70 000 people die of rabies every year. As the disease progresses of patients, more specific neurological symptoms were presented including such as insomnia, anxiety, confusion, slight or partial paralysis, excitation, hallucinations, agitation, difficulty swallowing, and hydrophobia (fear of water). Patients show severe paralysis gradually and eventually dead after a coma. Mice inoculated intramuscularly (i.m.) with CVS-11 (fix strain) showed the severe hind limb paralysis on 7 days and then dead eventually, however mice inoculated with CVS-11 intracerebrally (i.c.) were dead without limb paralysis (Kojima et al. 2009 and Sugiura et al. 2011). For understanding of hind limb paralysis, mice inoculated with CVS- 11, i.m. and i.c. was comparatively analysed by microarray and hisotopathology. Brains and spinal cords of mice were separatively collected after 7 days of the postinoculation of i.m. and i.c.. Viral antigens was similarly observed in both of brains and spinal cords in mice inoculated i.m. and i.c.. Pathologically, microglia was infiltrated in spinal cords in mice inoculated i.m. not but i.c.. In microarray, expression level of genes was normalized with each mock. After comparative analysis of gene expression in mice inoculated i.m. and i.c., significantly (fold change >2, /p/